2018
DOI: 10.1002/mp.13074
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation profile matching: An accurate and scan parameter‐robust measurement method for small airway dimensions in low‐dose CT scans

Abstract: Our proposed APM method has the potential to overcome the resolution limitations of current CT systems and accurately determine the small airway dimensions in COPD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Experimental methods for patient-specific QA in advanced radiotherapy are, however, time-consuming in both manpower and accelerator time and have been shown to be unable to detect some unacceptable plans. [6][7][8][9][10][11] Recent studies have demonstrated a sensitivity of only 5% to detect IMRT plan errors using IMRT pretreatment measurements. 12,13 Moreover, as treatment planning becomes more efficient and the number of patients treated with advanced radiotherapy techniques steadily increases, measurement-based verification may result in a continued increase in workload.…”
Section: Review Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental methods for patient-specific QA in advanced radiotherapy are, however, time-consuming in both manpower and accelerator time and have been shown to be unable to detect some unacceptable plans. [6][7][8][9][10][11] Recent studies have demonstrated a sensitivity of only 5% to detect IMRT plan errors using IMRT pretreatment measurements. 12,13 Moreover, as treatment planning becomes more efficient and the number of patients treated with advanced radiotherapy techniques steadily increases, measurement-based verification may result in a continued increase in workload.…”
Section: Review Of the Problemmentioning
confidence: 99%
“…1,3 Despite accurate CT assessments of larger airways with thicker walls, the cross-sectional pathological features in small airways with internal diameters of less than 2 mm have shown to be more critical to airway function. 9,[11][12][13][14] Due to the spatial resolution limitations of CT techniques in the clinical setting, partial volume effects reduce measurement accuracy for both lumen diameters and wall thicknesses. 12 Hence, the assessment of small airway dimensions up to the 6th generation (~2.5 mm in inner diameter) or higher generations remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The segmentation of small and peripheral airways is not a trivial task. 5,48,80 In this paper, we analyse the reproducibility of all computerized components of the tapering algorithm. The paper does not address reproducibility of manual labelling of the airways.…”
Section: Limitationsmentioning
confidence: 99%
“…Computed tomography (CT) is widely used for diagnosis, patient evaluation, and monitoring of body composition changes. Volumetric techniques are essential for diagnostic purposes, and recent efforts focus on deriving non-invasive imaging biomarkers for various diseases [ 1 , 2 ]. Hounsfield unit values enable assessment of the muscle, adipose tissue, and bone structures’ volume and status.…”
Section: Introductionmentioning
confidence: 99%